Numerical simulation of periodic cracking mechanism in microscopic surface films during roll bonding processes. Issue 8 (7th August 2019) - Khaledi, K.; Brepols, T.; Reese, S.
Abstract: The microscopic surface films existing on the top of metallic layers play an important role in the process of joining by plastic deformation. The bond formation during cold welding processes is basically associated with the fracturing of surface films to produce intimate metallic contacts. The present paper aims at providing a numerical model to describe the cracking pattern of brittle surface films bonded to the ductile substrates. A microscale finite element model is developed which takes into account the fracturing mechanisms of thin surface films in roll bonding processes. The presented model is calibrated by using the existing experimental data for an aluminum alloy covered by a thin layer of oxide film. The model is also validated against a well‐known analytical model for periodic cracking. The distribution of stresses within the fractured surface film demonstrates that the generated cracks in the surface film have essentially a periodic pattern. Moreover, it is shown that the crack spacing is highly dependent on the properties of the surface film. Finally, the obtained results for the roll bonding show that a crack density saturation takes place at the entry of the roll bite where a small surface expansion is applied to the rolled samples.